Deep-breathing Fe-doped superstructure modified by polyethyleneimine as oxygen reduction electrocatalysts for Zn–air batteries. Issue 32 (3rd August 2022) - Li, Yang; Liu, Jun; Zheng, Lingcheng; Zhang, Yanyan; Zhou, Wenhan; Shi, Kejian; Xu, Haiyu; Gao, Juan
Abstract : The development of economical, robust and highly active non-precious metal oxygen reduction reaction (ORR) electrocatalysts to replace precious metal catalysts is crucial for the widespread applications of metal–air batteries. Abstract : The development of economical, robust and highly active non-precious metal oxygen reduction reaction (ORR) electrocatalysts to replace precious metal catalysts is crucial for the widespread applications of metal–air batteries. Herein, a method for the modification of carbon by polyethyleneimine (PEI) is reported for the fabrication of Fe-doped three-dimensional (3D) porous carbon materials (defined as cal-FeZIF-NSC). Benefiting from the special N, S-co-doped 3D interconnected structure with high conductivity, which enhanced the accessibility to the active sites by "exhaling/inhaling" reactants and products, and Fe doping after modification with PEI, the newly prepared cal-FeZIF-NSC catalyst exhibited remarkable ORR catalytic activity in alkaline electrolyte with a high half-wave potential ( E 1/2 ) of 0.8 V (approaching that of Pt/C) and good stability (only 28 mV decline of E 1/2 after 10 000 cycles). As a proof of concept, a Zn–air battery was further assembled using cal-FeZIF-NSC-0.2 as air cathodes, which exhibited a large specific capacity of 744 mA h g −1 and long-term cycling stability (90 cycles/30 h), superior to that of commercial Pt/C–RuO2 catalysts, demonstrating the considerable application potential of this catalyst. This simple synthesis strategy may provide a new idea to fabricate Fe-doped catalysts for energy storage and conversion applications.